Redescription and biogeography of Mabuya cochabambae Dunn with comments on Bolivian congeners (Lacertilia: Scincidae) - Harvey, Michael B.; Aguayo, Rodrigo; Miralles, Aurélien (Zootaxa, 2008)
On the basis of new material, observations in the field, and data from living specimens, we redescribe Mabuya cochabambae Dunn and discuss its distribution and biogeography. Morphological and molecular evidence strongly suggests that M. cochabambae and M. dorsivittata are sister taxa. In addition to M. cochabambae, we tabulate morphological data for three other Mabuya occurring in Bolivia: M. dorsivittata Cope, M. frenata (Cope), and M. guaporicola Dunn. Mabuya altamazonica Miralles et al. and M. nigropunctata (Spix) both occur in Bolivia, specimens of the former coming from the western lowlands and of the latter from the eastern lowlands of central Santa Cruz. Finally, we propose a new key to the eight species of Mabuya occurring in Bolivia.